CURRENT ASPECTS OF EPIDEMIOLOGICAL AND CLINICAL ISSUES OF EPSTEIN-BARR VIRUS INFECTION IN CHILDREN - Rabbimova Nodira Tashtemirovna (Web of Journals Publishing, 2024)
This article discusses the clinical presentation of infectious mononucleosis in 142 children aged between 1 and 14 years living in the Samarkand region. It was determined that the disease continues to manifest all its characteristic clinical features at present. Timely and accurate diagnosis of infectious mononucleosis leads to effective treatment, demonstrated by a decrease in fever duration, a reduction in the severity of lymph node proliferation, and a quicker resolution of the cytolytic process.
Keywords: Atypical mononuclear cells, children, Epstein-Barr virus (EBV), infectious mononucleosis.